2022
DOI: 10.2478/picbe-2022-0057
|View full text |Cite
|
Sign up to set email alerts
|

The importance and interdependence of key bioeconomy concepts: A bibliometric analysis

Abstract: Environmental well-being has recently been put at risk due to unsustainable industrial practices. The relevant decision-makers have developed policies to support a greener approach in the economy. This paper aims to present a complete and comprehensive connection between the key concepts of the economy based on biological resources from both empirical and analytical perspectives by highlighting the structure, importance, and evolution. Through bibliometric research and network mapping analysis, we have reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…An overview of the links between the concepts connected with the circular economy was made by Grădinaru & Matei (2022). Figure 1 highlights all the links presented previously, but also the subsequent developments, due to digitization and sustainable development.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…An overview of the links between the concepts connected with the circular economy was made by Grădinaru & Matei (2022). Figure 1 highlights all the links presented previously, but also the subsequent developments, due to digitization and sustainable development.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Source: Grădinaru & Matei, 2022 The view based on theoretical studies was practically demonstrated through an analysis of all published articles in each of the mentioned fields. In our case, the circular economy influences and is influenced by the bioeconomy, the green economy, the circular bioeconomy, and the digitized circular bioeconomy.…”
Section: Figure No 1: Conceptual Framework Of Circular Economymentioning
confidence: 99%